Pengaruh reminiscence therapy terhadap tingkat stres pada lansia masa pendemi covid-19 - Ikhsan Ikhsan; Septi Andrianti; Titin Aprilatutini (Holistik Jurnal Kesehatan, 2022)
Reminiscence therapy interventions for Chronic stress in elderly during pandemic covid-19 Background: The level of stress in the elderly also means the level of pressure felt or experienced by the elderly. During the COVID-19 pandemic, the government recommends social distancing. In addition, self-quarantine has almost a year. Conditions of social distancing or physical distancing can trigger psychological pressure, especially for the elderly who live in orphanages and have chronic diseases. Purpose: To determine the effect of Reminiscence therapy interventions for Chronic stress in elderly during pandemic covid-19Method: This research is a pre-experimental design with a one-group pretest and posttest design. The population is 65 elderly, using purposive sampling. This research was 30 elderly, 15 elderly in the control group, and 15 elderly in the intervention group. The instrument is the DASS (stress scale) questionnaire. Data analysis used the Paired Sample t-Test statistical test. The research was done on April June 2021.Results: Finding that the average stress score before and after which in the control group the stress score was before 27.81 with a standard deviation of 4.34 and in the eighth week the stress score decreased to 24.64 with a standard deviation of 4.74. In the intervention group, the stress score before 28.31 with a standard deviation of 4.44 and after being treated for eight weeks decreased to 14.80 with a standard deviation of 5.86. Evidenced by the p-value of 0.001 (α <0.05).Conclusion: The experience of the stress by the elderly with an average standard deviation of 65-89 years. The stress score before reminiscence therapy was 28.31 with a standard deviation of 4.44, and after 8 weeks of reminiscence therapy, it decreased to 14.80 with a standard deviation of 5.86.Keywords: Reminiscence therapy; Chronic stress; Elderly;  Pandemic covid-19Pendahuluan: Tingkat stres pada lansia juga berarti tingkat tekanan yang dirasakan atau dialami oleh lansia. Selama pandemi COVID-19, pemerintah merekomendasikan jarak sosial. Selain itu, karantina mandiri telah dilakukan selama hampir satu tahun. Kondisi social distancing atau jarak fisik dapat memicu tekanan psikologis, terutama bagi lansia yang tinggal di panti asuhan dan memiliki penyakit kronis. Tujuan: Mengetahui pengaruh Terapi Reminiscence terhadap tingkat stres pada lansia pada masa pandemi Covid 19 di Panti Sosial Tresna Werdha Kota Bengkulu Tahun 2021.Metode: Penelitian pre-experimental design dengan one-group pretest and posttest design. Populasi adalah 65 partisipan, dengan menggunakan purposive sampling. Penelitian ini berjumlah 30 lansia, 15 lansia pada kelompok kontrol dan 15 lansia pada kelompok intervensi. Instrumen yang digunakan adalah kuesioner DASS (skala stres). Analisis data menggunakan uji statistik Paired Sample t Test. Penelitian direncanakan akan dilaksanakan pada bulan April Juni 2021.Hasil: Didapatkan bahwa rata-rata skor stres sebelum dan sesudah pada kelompok kontrol skor stres sebelum 27,81 dengan standar deviasi 4,34 dan pada minggu kedelapan skor stres menurun menjadi 24,64 dengan standar deviasi 4,74. Pada kelompok intervensi, skor stres sebelum 28,31 dengan standar deviasi 4,44 dan setelah diberi perlakuan selama delapan minggu menurun menjadi 14,80 dengan standar deviasi 5,86. Dibuktikan dengan nilai p sebesar 0,001 (α < 0,05).Simpulan: Stress dialami oleh lansia dengan usia rata-rata standar deviasi 65-89 tahun. Skor stress sebelum reminiscence therapy adalah 28.31 dengan standar deviasi 4,44, dan setelah dilakukan reminiscence therapy  selama 8 minggu terjadi penurunan menjadi 14,80 dengan standar deviasi menjadi 5,86.